Harmonization of the Implementation of Restorative Justice Regulations in Law Enforcement of Property Crimes in the Indonesian Criminal Justice System - Agus Sumartono (Lembaga Bale Literasi, 2026)
The purpose of this study is to examine the regulations in criminal settlement actions through the restorative justice approach, which still causes a perception of the system in Indonesian criminal law. This concept is part from policy criminal background? philosophy, shifting punishment? to a philosophy of restorative. Research This use approach juridical normative referring to law? written in the regulations legislation, as well as empirical, such as the implementation difference settlement cases that use the restorative justice subsystem? justice. Research results show implementation of the enforcement law through the restorative not optimal, especially in the stages of the investigation, inquiry, prosecution, trial, reporting, and settlement database processes. The restorative justice approach has not been fully integrated that has not been effectively fixed law. In this research, the author offers draft harmonization regulations, arrangement, settlement action criminal through justice restorative, which becomes guidelines in settlement action criminal or case in the system justice in Indonesia after the enforcement of Constitution Number 1 of 2026 concerning the Criminal Procedure Code.